ANALISIS YURIDIS KEPASTIAN HUKUM PARATE EKSEKUSI TERHADAP BARANG JAMINAN FIDUSIA YANG DIALIHKAN OLEH DEBITUR KEPADA PIHAK KETIGA (STUDI PT. OTO MULTIARTHA MEDAN) - ROCKY JHONSON SITUMEANG (PREMISE LAW JURNAL, 2017)
ABSTRACT In its implementing parate execution, it usually undergoes many obstacles so that it does not protect PT. OTO Multiartha. In fact, according to Law on Fiduciary Collateral, the company is protected by law with fiduciary collateral which has executorial title power. The research used judicial normative method. The data were gathered by conducting library research and interviews in which the materials or data were organized systematically and analyzed by using scientific logical procedure qualitatively. Conclusion From thesis singer is the implementation of parate execution by PT. OTO Multiartha, Medan, on fiduciary collateral which was transferred by debtors to the third party was ineffective because the third party that received and controlled the fiduciary collateral rejected. In this case, legal remedy carried out by PT. OTO Multiartha, Medan, was that it used non-litigation method by performing reconciliation. Keywords : Fiduciary Collateral, Parate Execution, Transferre.